Fish assemblages along the coasts of Tunisia: a baseline study to assess the effectiveness of future Marine Protected Areas - BEN LAMINE, EMNA; GUIDETTI, PAOLO; ROMDHANE, MOHAMED SALAH; FRANCOUR, PATRICE (Mediterranean Marine Science, 2018)
The present study investigated coastal fish assemblages, using Underwater Visual Census (UVC) transects, in Tunisia (south Mediterranean basin). The rationale behind this work is to get i) a suggestive evidence about the status of fish assemblages, and ii) baseline data at 3 locations in Tunisia where 3 MPAs will be established, before the implementation of protection measures. At each location, we used a sampling design where fish censuses were performed in two types of zone: zones that will be inside MPAs, and zones that will remain outside. On the whole, 49 taxa belonging to 19 families were censused. Data reveal clear symptoms of overfishing, especially in terms of dominance of small- and medium-sized individuals of commercially relevant species. Our analyses, moreover, did not show any significant difference in whole fish assemblage structures (considering both density and biomass), patterns of average species richness, total fish density and biomass, density and biomass of different trophic categories of fishes, size distribution of commercially relevant species, between future-protected and unprotected zones. Overall, results suggest that 1) current fish assemblages at the three studied locations are likely to be seriously impacted by fishing activities, and 2) these data could be used as reliable baselines to assess the effectiveness of protection measures within the MPAs that will be established in the future. Our study is the first in Tunisia, and in North African coasts, that assessed distribution patterns of coastal fish assemblages by means of UVC, using a formal spatially replicated sampling design for resource management.